Legal Validity with Artificial Intelligence Technology on Gpt Chat as Legal Aid - Ahzaza Fahrani; Gunawan Djajaputra (Dinasti Research, 2024)
The use of Artificial Intelligence (AI) technology, such as ChatGPT, in providing legal assistance in Indonesia presents new potential for improving accessibility and efficiency. However, there remains uncertainty regarding the legal liability for errors that may occur in the legal advice provided by AI. This study aims to explore the legal validity of using AI in providing legal aid and to examine how legal liability may be attributed to service providers if mistakes occur. By reviewing Law No. 18 of 2003 on Advocates, Law No. 8 of 1999 on Consumer Protection, and Law No. 27 of 2022 on Personal Data Protection, this study highlights the importance of specific regulations to ensure that AI use in legal assistance adheres to legal and ethical standards. Additionally, the study discusses legal protection for AI service users, particularly regarding personal data security and consumer rights. The conclusion emphasizes the need for a clear regulatory framework to ensure that AI use in the legal field provides optimal benefits without compromising security and legal certainty for users.